Sexuality and mental health during the pandemic: Associations among couples' COVID-19 anxiety, sexual communication, and sexual satisfaction. Issue 5 (20th October 2022) - Denes, Amanda; Cornelius, Talea; Guest, Chelsea; Webber, Katrina T.; Gorin, Amy A.
ABSTRACT: The present study explored the associations among COVID-19 anxiety, sexual communication, and sexual satisfaction in couples cohabitating together during the pandemic lockdown. Forty-one couples living in three major cities in the United States completed a survey during the early months of the pandemic. Multilevel modeling revealed that individuals' sexual communication was associated with their own, but not their partner's, reported sexual satisfaction. However, COVID-related anxiety was not indirectly associated with sexual satisfaction through sexual communication nor did it moderate the association between sexual communication and sexual satisfaction. These findings reveal that the well-established link between sexual communication and sexual satisfaction remained during the pandemic and that anxieties related to the pandemic did not impact this association.